Giant Splenic Artery Aneurysm – An Analysis of the Recent Literature - Salati, Sajad Ahmad; Rather, Ajaz Ahmad (Lietuvos chirurgija, 2024)
Objective. This article was composed to review the profile of giant splenic artery aneurysm as reported in the recent literature. Methodology. A systematic literature search was conducted through electronic databases and scientific networking sites, including PubMed, Scopus, and Google Scholar, using the key words and terms “giant splenic artery aneurysm”, “large splenic artery aneurysm”, and “huge splenic artery aneurysm”. Only literature in English was considered for inclusion in this study, and the time frame was fixed between 2014 and 2024. Results. 16 cases, including 9 (56.25%) females and 7 (43.75%) males, ranging in age from 35 to 84 years (mean 60.4±13.4 years). Years were included in the review. The size of aneurysm varied from 10 cm to 30.68 cm (mean 12.54±5.32 cm). Upper abdominal pain was the commonest presentation, along with shock and palpable lumps. The majority of the cases (n = 11; 68.7%) were managed by laparotomy, and an endovascular approach was adopted in 4 (25%) cases. Conclusion. Giant splenic artery aneurysm (GSAA) is a rare but potentially life-threatening condition. Physicians need to be aware of this condition so that a diagnosis is made promptly. There is no role of conservative management, and all giant aneurysms need appropriate treatment after detection. Open surgical aneurysmectomy is the mainstay of management.